Auditee's intention to implement audit recommendations: A qualitative study based on the theory of planned behavior - Rahandiani, Dewi; Ritonga, Irwan Taufiq; Imansantosa, Prabowo (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2024)
Previous studies on the implementation of audit recommendations have primarily focused on identifying influencing factors without delving into the specific behaviors of individuals responsible for their implementation. This study aims to analyze auditees' intentions to implement audit recommendations using Ajzen's Theory of Planned Behavior (TPB). While TPB is typically applied with quantitative methods, this research employs a qualitative approach to gain a deeper understanding of respondents' attitudes, motivations, and values. The findings reveal five main themes that influence auditees' intentions to implement audit recommendations: lack of engagement, unorganized organizational pathways, the role of decision-makers or policymakers, mutual reluctance toward coordination, and gaps in knowledge and qualifications. Addressing these themes simultaneously is essential for the effective implementation of audit recommendations. Auditees' attitudes toward implementing audit recommendations significantly impact their intentions. However, subjective norms and perceived behavioral control can pose barriers, diminishing their commitment to the implementation process. This nuanced understanding of the factors affecting auditee behavior is crucial for developing strategies to enhance compliance with audit recommendations.